Adsorption of Bemacid Red by Poly Tetra (Ethylene Glycol) Dimethacrylate Crosslinked with 2-Hydroxypropyl Methacrylate Hydrogels: Equilibrium and Kinetic Studies - Zoubida Seghier; Abdelkader Iddou; Laura Caserta; Asmahane Fasla (Indonesian Journal of Chemistry, 2022)
Besides others, textile industries are the primary sources of discharging a massive amount of highly colored wastewater. Adsorption can be considered the most economically favorable technology method for removing dyes from wastewater. This paper reports the synthesis of Poly tetra (ethyleneglycol) dimethacrylate crosslinked with 2-hydroxypropyl methacrylate (Poly (TtEGDMA-cross-2-HPMA)) hydrogelsand its application as a novel sorbent to remove bemacid red (ET2) dye from aqueous solution under various operating conditions. The equilibrium adsorption capacity was found 142.82–883.60 mg ET2 g–1 of 1% TtEGDMA. The adsorbent was characterized using Fourier transform infrared radiation (FTIR) and 13carbon solid-state nuclear magnetic resonance spectra (13C-NMR). The effects of the experimental parameters include dye concentration and crosslinked agent concentration. The kinetic sorption uptake for ET2 by Poly (TtEGDMA-cross-2-HPMA) at various initial dye concentrations was analyzed by pseudo-first and pseudo-second models. Two sorption isotherms, namely the Langmuir and Freundlich isotherms, were applied to the sorption equilibrium data. The sorption kinetics of ET2 onto the hydrogels followed the pseudo-second-order kinetics model (R2 = 0.999) and the adsorption equilibrium data obeyed the Langmuir isotherm model (R2 = 0.999). It can be concluded that Poly (TtEGDMA-cross-2-HPMA) is an alternative economic sorbent to more costly adsorbents used for dye removal in wastewater treatment processes.